Estudo etnográfico das experiências de três mulheres brasileiras que transformaram seus estilos de vida - Job, Maria Carmencita da Felicidade (2021)
In this ethnographic research, I analyze the trajectories of three Brazilian middle-class women, two of them white and one brown, with a high level of education, cultural capital and a broad professional trajectory who, in recent years, consciously chose to create new ways of living due to of a feeling of “disembedding” (GIDDENS, 1991). I investigate their trajectories from three dimensions: 1. Change Processes; 2. Economic Practices; 3. Forms of Activism. Reflecting on actions that can mobilize care for themselves and their local communities, I chose to observe them in a participatory manner. At first, through digital ethnography, from the “perambulations” in their social networks, “immersions”, “accompaniments” and digital interviews (LEITÃO, 2018). In a second moment, I accompanied the interlocutors in person, in their spaces of coexistence and sociability, observing their routines. I chose to describe their activities, through social scenes, starting from the ethnography of perceptions, by Florence Weber (2009), where I could perceive with more intensity their identities and projects, both in the personal and professional spheres, and their possible forms of activism. The selected scenes, understood as paradigmatic of their lifestyles as they manifested mobilizations, circuits and multiplication of care, sought to identify whether the networks of (selected) interlocutors sensitize other women; and whether there was a connection between their practices and a feminist and ecological activism that would foster care networks marked by projects focused on socio-environmental, economic and political care. The intention of the work was to investigate whether the revisions of the interlocutors' lifestyles would have broader implications in the construction of processes for transforming the concept of “Bem Viver”, under discussion and under construction by the economist Alberto Acosta (2016). Since the notion of Bem Viver is a vision that comes from indigenous peoples, based on the relationship and on a participatory, community-based way of living in balance with nature.